Three sisters - Doss, James D. (Doss, James D. Charlie Moon mystery., 2007)
With the help of his aunt Daisy Perika, a Ute shaman, part-time tribal investigator Charlie Moon and his friend, Granite Creek, Colorado, police chief Scott Parris, investigate the vicious murder of a woman, one of three daughters of a wealthy rancher.